Copeptin is increased by nausea and vomiting during hypertonic saline infusion in healthy individuals. (4th February 2021) - Brooks, Emily; Bachmeier, Caroline; Vorster, Juanita; Sorbello, Jane; Peer, Faseeha; Chikani, Viral; Dimeski, Goce; Ungerer, Jacobus; Pretorius, Carel; Inder, Warrick
Summary: Objective: Measurement of hypertonic saline‐stimulated copeptin has recently been described for the differentiation of polyuria‐polydipsia syndrome. This study aims to determine the copeptin response to intravenous 3% hypertonic saline, including evaluation of adverse effects, in a local cohort of healthy adults >18 years in Australia. Design: Prospective clinical study. Methods: Twenty healthy volunteers (10 males and 10 females) were recruited. Participants underwent infusion of 3% hypertonic saline via a previously described standardized protocol, until the plasma sodium was ≥150 mmol/L, with measurement of plasma copeptin. Results: Mean peak sodium was 152 mmol/L ± SD 1.4 with osmolality 315 mmol/kg ± SD 3.9. Median volume of hypertonic saline infused to reach target sodium ≥ 150 mmol/L was 1536 mL (IQR 1362, 1992). Mean rate of plasma sodium rise was 5.9 mmol/L/hour ± SD 1.5. Hypertonic saline‐stimulated copeptin had non‐parametrical distribution with median of 33.8 pmol/L (IQR 27.6, 63.6). Overall median symptom burden was 6/10 (range 3/10‐9/10). Copeptin was significantly higher for those who experienced nausea and/or vomiting (n = 13) (median 39.0 pmol/L; IQR 32.5, 90), compared to those participants who did not experience either (median 20.0 pmol/L; IQR 13.0, 31.0) ( P = 0.003). There were no serious adverse events. Conclusion: Hypertonic saline‐stimulated copeptin measurements were similar in our population compared with previously reported reference intervals in healthy volunteers. There is a wide range of stimulated copeptin measurements in the healthy population. Nausea and vomiting are common adverse effects which enhance the copeptin response.